ASSOCIATION OF HBA1C AND NEUTROPHIL LYMPHOCYTE RATIO WITH NORMAL-TENSION GLAUCOMA IN METABOLIC SYNDROME AND OBSTRUCTIVE SLEEP APNEA RISK PATIENTS - Prayitnaningsih, Seskoati; Asrory, Virna Dwi Oktariana; Nusanti, Synthia; Listyaningsih, Erlin; Siswanto, Bambang Budi; Santoso, Anwar (MNJ (Malang Neurology Journal), 2021)
Background: Normal-Tension_Glaucoma (NTG) is an eye disease and characterize with low intraocular pressure (IOP) levels. In population-based settings, the diagnose of glaucoma is based on the IOP levels of 21 mmHg, and its usually delayed. A recent study HbA1c levels could lead to IOP changes. Obstructive Sleep Apnea (OSA) result oxidative stress that results an altered function of neutrophil in patients with NTG. Objective: To_evaluate the association of HbA1c, Netrophil-to-Lymphocyte Ratio_(NLR) toward NTG as its novel early detection.Methods: This study divided into two groups consisted of Metabolic Syndrome ( MS) + OSA without eye disorder as control (15 subjects) and MS + OSA + NTG patients (14 subjects). IDF criteria was used to established MS, and risk of OSA determined by STOP-BANG Questionnaire. The diagnosis of NTG was confirmed by normal IOP measured by Tonopen. Mean Defect (MD) of visual field evaluated by Automated Humphrey Perimetry, Retinal Nerve Fiber Layer (RNFL) established by OCT. HbA1c measured by ELISA and NLR by flowcytometry. Statistical analysis consisted of comparison and correlation testResults: The ratio of CD was significantly higher in NTG patients (0.54 Â± 0.13) compared to control (0.26 Â± 0.07; p<0.001). MD was also higher in subjects with NTG (6.80 Â± 3.90) compared to control (4.97 Â± 2.28; p=0.134). Mean RNFL was lower in subjects with NTG (87.95 Â± 28.29) compared to control (95.07 Â± 26.66; p=0.035). Positive correlation between HbA1C-MD (r = 0.456, p = 0.013) and NLR-RNFL thinning (r = 0.525, p = 0.003) was existed in Metabolic Syndrome (MS) patients.Conclusion: Patients with MS and OSA risk have an increased risk of NTG. A novel association between Hba1C levels, NLR and NTG was also identiï¬ed.